1978
DOI: 10.1093/nar/5.3.1017
|View full text |Cite
|
Sign up to set email alerts
|

Poly(dG).poly(dC) at neutral and alkaline pH: the formation of triple stranded poly(dG).poly(dG). poly(dC)

Abstract: Alkaline titrations of different samples of poly(dG).poly(dC) and of the constituent homopolymers poly(dG) and poly(dC) have been performed in 0.15 M NaCl and their CD spectra followed. Sample I contained a slight excess of poly(dC) (52% C: 48% G) and showed a single reversible transition (pK = 11.9) due to the dissociation of double stranded poly(dG).poly(dC). Sample II, containing an excess of poly(dG) (43% C: 57% G), showed two transitions (pK1 = 11.4, PK2 = 11.9) the first one being only partially reversib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 9 publications
4
49
0
Order By: Relevance
“…Interestingly, an intense and negative ellipticity at 212 nm is induced upon triplex formation, as previously observed for other triplex structures [5,6,24]. Another outstanding feature present in the 20GT: 30RY spectrum is the presence of a negative ellipticity at 277 nm, which according to a study on poly(dG).poly(dC) has been attributed to the formation of triplex helices containing G. GC triads [20,21,32,33]. …”
Section: Polyacrylamide Gel Electrophoresis and Ha Chromatographysupporting
confidence: 66%
See 1 more Smart Citation
“…Interestingly, an intense and negative ellipticity at 212 nm is induced upon triplex formation, as previously observed for other triplex structures [5,6,24]. Another outstanding feature present in the 20GT: 30RY spectrum is the presence of a negative ellipticity at 277 nm, which according to a study on poly(dG).poly(dC) has been attributed to the formation of triplex helices containing G. GC triads [20,21,32,33]. …”
Section: Polyacrylamide Gel Electrophoresis and Ha Chromatographysupporting
confidence: 66%
“…The first evidence about the formation of R. RY triplexes was obtained with mixtures of poly(G) plus poly(C) [20,21] and poly(U) plus poly(A) [22]. Thereafter, Kohwi and KowhiShigematzu demonstrated that a segment of poly dG.…”
Section: Introductionmentioning
confidence: 99%
“…The hysteresis of poly(dG)-poly(dC) is complicated by the f6rmation of an acid complex at the beginning of the acid titration . Furthermore, we have shown that most samples of poly(dG)*poly(dC) contained two hetero-complexes, 8 poly(dG)*po1y(dC) and poly(dG).poly(dG)*poly(dC) The distribution of these C Information Retrieval Umited I Falconbwg Court London W1V 5FG England…”
Section: Introductionmentioning
confidence: 99%
“…Two structural motifs by which these triple helices form have been described. The more widely studied motif is based on Hoogsteen hydrogen bonding of a pyrimidine oligonucleotide wherein T recognizes A-T base pairs and protonated C (C+) recognizes G-C base pairs (1)(2)(3)(4)(5)(6). The ODNs bind in the major groove of DNA such that the pyrimidine ODN is parallel to the purine strand of the duplex.…”
mentioning
confidence: 99%